Intergenerational bonding in family and school contexts: which does impact more on degree aspiration of students? - Shahidul, S. M.; Karim, A.H.M Zehadul (Canadian Center of Science and Education, 2015)
Among the factors which have trajectory roles on the academic attainment of students, intergenerational bonding is the foremost of them. Though intergenerational bonding has basically focused on parent-child relationship, contemporary studies further consider the teacher-student relationship as intergenerational bonding to identify its effect on the academic attainment of students. In this study, we first examine both types of bonding which are created by parent-child and teacher-student relationships and how these impact on the degree of aspiration of secondary school students. Then, we compare these effects to identify which factor affects more on the degree aspiration outcome of students. We use the data collected from 553 students of Grade IX from 12 secondary schools in Bangladesh. The effect size of parent-child bonding and teacher-student bonding are compared using standardized Beta (β) weights of these two variables. The results show that beyond the socioeconomic status, both parent-child bonding and teacher-student bonding significantly and positively impact on students' degree aspiration outcome. Furthermore, when we compared the effect size of these two variables, results show that parent-child bonding had more strength compared to teacher-student bonding to predict the degree aspiration outcome of students.